The influence of lower-limb dominance on postural balance - Alonso, Angélica Castilho; Brech, Guilherme Carlos; Bourquin, Andréia Moraes; Greve, Julia Maria D’Andréa (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Maintainance of postural balance requires detection of body movements, integration of sensory information in the central nervous system and an appropriate motor response. The purpose of this study was to evaluate whether lower-limb dominance has an influence on postural balance. DESIGN AND SETTING: This was a cross-sectional study conducted at Faculdade de Medicina da Universidade de São Paulo (FMUSP) and at Hospital do Coração (HCor). METHODS: Forty healthy sedentary males aged 20 to 40 years, without any injuries, were evaluated. A singlefoot balance test was carried out using the Biodex Balance System equipment, comparing the dominant leg with the nondominant leg of the same individual. The instability protocols used were level 8 (more stable) and level 2 (less stable), and three instability indices were calculated: anteroposterior, mediolateral and general. RESULTS: The volunteers’ mean age was 26 ± 5 years (range: 20-38), mean weight 72.3 ± 11 kg (range: 46-107) and mean height 176 ± 6 cm (range: 169-186). Thirty-four of them (85%) presented right-leg dominance (defined according to which leg they used for kicking) and six (15%) had left-leg dominance. There were no significant differences between the dominant and nondominant legs at the two levels of stability (eight and two), for any of the instability indices (general, anteroposterior and mediolateral). CONCLUSION: The lower-limb dominance did not influence single-foot balance among sedentary males.